Fruiting phenology and dispersal syndromes in a sandy coastal plain in southeastern Brazil - Patrick de Oliveira; Cristine Rodrigues Benevides; Alexandre Verçosa Greco; Luciene Campos São Leão; Ana Tereza de Araújo Rodarte; Heloisa Alves de Lima (Rodriguésia, 2022)
Abstract Fruits have a wide variety of morphological and phenological characteristics that have been related to environmental conditions and seed dispersal mode. In this paper, we describe the fruit morphology, the fruiting phenology and infer dispersal patterns of 52 species from restinga of Maricá, Rio de Janeiro, in order to understand the richness and temporal variation of these resources in the community. Fleshy, indehiscent, and colored fruits, typical of zoochory, predominate in the restinga (77.8%). Anemochoric fruits represent 13.3%. In 42% of zoochoric species, fruits go through three to five colors until maturity, and different stages of ripeness can be observed on the same plant. A constant supply of zoochoric and anemochoric fruits was observed throughout the year. Unlike flowering, there were no significant correlations between fruiting activity and intensity and abiotic factors. For the community studied, the fruiting pattern observed also contrasts with flowering, due to the lower seasonality, and intensity suggesting that biotic factors, such as seed dispersers (in the case of zoochoric fruits) may have relevance in determining fruit ripening and seed dispersal periods in coastal environments.